The epidemiology of falls in Portugal: an analysis of hospital admission data - Sampaio, Filipa (2021)
Copyright: © 2021 Sampaio et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.